Optic Nerve Ultrasound Evaluation in Animals and Normal Subjects - Vitiello, Livio; De Bernardo, Maddalena; Capasso, Luigi; Cornetta, Palmiro; Rosa, Nicola (Frontiers in Medicine, 2022)
In recent years, ultrasonographic measurement of the optic nerve sheath diameter has been widely used to identify the presence of increased intracranial pressure. Intracranial hypertension is a life-threatening condition that can be caused by various neurological and non-neurological disorders, and it is associated to poor clinical results. Ultrasonography could be used to qualitatively and efficiently detect intracranial pressure increases, but to reach this purpose, clear cut-off values are mandatory. The aim of this review is to provide a wide overview of the most important scientific publications on optic nerve ultrasound normal values assessment published in the last 30 years. A total of 42 articles selected from PubMed medical database was included in this review. Our analysis showed that ocular ultrasonography is considered to be a valuable diagnostic tool, especially when intracranial hypertension is suspected, but unfortunately this research provided conflicting results that could be due to the different ultrasound protocols. This is mainly caused by the use of B scan alone, which presents several limitations. The use of B-scan coupled with the standardized A-scan approach could give more accurate, and reliable ultrasound evaluation, assuring higher data objectivity.